PERANCANGAN ALAT PELUBANG, PEMOTONG DAN PEMATAH KERTAS 3 IN 1 MENGGUNAKAN METODE ERGONOMICFUNCTION DEPLOYMENT ( EFD ) - Khairul Ihwan; Muhammad Rozie (Program Studi Teknik Industri, 2017)
Hollowing, Cutting and Breaking paper is an activity that is closely related to the world of Printing. In the world of printing that has been modern today the printing tools continue to evolve to follow the modern era. The products that are designed in this research are 3 hole punching and cutting tools. The method used in this planning uses the measurement of EFD method technique parameters, the application of ergonomics, anthropometry processing, validity and reability test. The results obtained by the designer from the design The 3 in 1 piercing, cutting and paper-splitting device is on the product using materials in the form of Iron and plastic. In the design can be folded and arranged according to our wishes. Tool height 41.5 cm, Tool length 58 cm and has a width of 33 cm. In addition to this table has more than one function that is in addition to melaukuan process perforation on paper, this tool can da da cutting process and also the process of folding the paper fold.